Rancang Bangun Sistem Register Surat Masuk Berbasis Web untuk Mengoptimalkan Pengelolaan Agenda pada Bri KCP Jelutung - Apriliani Sulistiawati; Noneng Marthiawati; Kevin Kurniawansyah; Novitasari Novitasari (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2026)
This study aims to design a web-based incoming mail registration system to improve the effectiveness of document archiving at BRI KCP Jelutung. Currently, incoming mail records are managed manually using an agenda book, resulting in slow archive retrieval and increasing the risk of document damage or loss. The research was conducted through observation and user requirements analysis of the incoming mail management process. The result is a web-based system design capable of recording incoming mail data in a complete and structured manner. The system is also equipped with an integrated document scanning feature, allowing physical documents to be digitized and stored automatically in a database without requiring a separate upload process. Scanned documents can be accessed at any time through the system, making archive retrieval and management faster and more efficient. The proposed system is expected to create a more efficient, organized, and transparent mail administration process at BRI KCP Jelutung. Furthermore, the research results can serve as a reference for future system development and implementation within the institution.